Methodology for the development of electronic prototypes integrating hardware and software. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
The article presents a methodological proposal for developing prototypes that integrate hardware and software. Thisproposal starts with the identifying the differences and similarities presented in the development of firmware andelectronic hardware, and the complications of their integration into a prototype. It is based upon insights from pragmaticprogramming, agile and cyclical methodologies for software development, the Bottom-Up strategy used in hardwaredevelopment, and some activities from the Out-In methodology. The methodology is divided into phases and stages.The initialization phase comprises the stages of story, analysis, and tracer bullet. The development phase consists ofa sprint that commences with the tracer bullet, followed by several sprints of the construction stage, then the integrationstage, and culminates with the laboratory testing stage. The verification stage combines the demonstration and deliverystage. If the prototype requirements are not met, one can return to the development phase and iterate again. Themethodology was applied in the development of a prototype, yielding satisfactory results in meeting the requirementsand in execution time. It is concluded that it is feasible to obtain a prototype integrating hardware and software at aTRL6 maturity level within a specific timeframe, through the proposed methodology in a collaborative and iterative workenvironment.
Keywords: Firmware; Electronics; Agile Methodologies; Sprint